Bullying Prevention Focused Interventions in Adolescents: A Scoping Review - Hikmat, Rohman; Suryani, Suryani; Yosep, Iyus; Jeharsae, Rohani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Bullying in adolescents is a serious problem that has a negative impact on the victim's mental health, academic performance and social relationships. Bullying prevention efforts are very important to create a safe and supportive school environment. Although many interventions have been developed, their effectiveness varies, and there remains a gap in the literature regarding the best approaches to preventing bullying in adolescents. Objective: This study aims to explore existing bullying prevention interventions and assess their effectiveness through a scoping review. Method: The method used is a scoping review by searching for articles from three main databases, namely Scopus, PubMed, and CINAHL, as well as one search engine, Google Scholar. Keywords used included “bullying prevention,” “adolescents,” “intervention,” “school,” and “community.” Inclusion criteria included studies involving adolescents aged 12–18 years, focused on bullying prevention interventions, and published in English. Data was analyzed descriptively qualitatively. Results: The results show that there are six articles that discuss interventions to prevent bullying in adolescents. The results of this study indicate that education, role play, and group discussions can significantly prevent bullying behavior. This success is due to a comprehensive approach involving all stakeholders and the use of interactive methods that encourage active student participation. Variables that influence intervention effectiveness include social support, student engagement, and consistency of program implementation. Conclusion: The implementation of interventions must be consistent and sustainable, as well as the involvement of all relevant parties, is very important to achieve optimal results.